Relations of radio sources with jets parameters - Miroshnichenko, A.P. (Кинематика и физика небесных тел, 2005)
We considered the sample of galaxies and quasars with jets based on observed data. We obtained the magnetic field strength in these objects using the condition of energy equipartition between the relativistic particles and the magnetic field. We determined values of luminosities in the radio band and in optics. The relations of the sample object radio sizes, luminosities, spectral indices, redshift were derived. An estimations of the lifetime for objects with jets were obtained too.